COMPUTER ASSISTED LANGUAGE LEARNING (CALL) AS EFL TEACHING AND LEARNING MEDIA IN INDONESIA: OPPORTUNITY AND CHALLENGES - Umi Rachmawati (Universitas Islam Nahdlatul Ulama Jepara, 2016)
Information and communication technology has been growing faster and larger in education in general and in English language teaching in particular. The use of this media is supported by the behaviorist due to its beneficial impacts for the teaching and learning processes. In Indonesian context, the use of computer assisted language learning has been implemented during the teaching and learning processes though many teachers and students do not have sufficient competence. Thus is due to the curriculum requires the teachers to make benefits from the media. In fact, there are many obstacles found by both teachers and students in implementing the media. Therefore, in this writing, the writer make theoretical review on the implementation of computer assisted language learning during the teaching of English in terms of its opportunities and challenges. All parties involved in the teaching and learning processes should correspond the benefits of the media and the challenges of the media use in order to accelerate the success of EFL teaching and learning.